Efficacy and Safety of Cordyceps militaris as an Adjuvant to Duloxetine in the Treatment of Insomnia in Patients With Depression: A 6-Week Double- Blind, Randomized, Placebo-Controlled Trial - Zhou, Jiaojiao; Chen, Xu; Xiao, Le; Zhou, Jingjing; Feng, Lei; Wang, Gang (Frontiers in Psychiatry, 2021)
Background: Insomnia is a common clinical manifestation in patients with depression. Insomnia is not only a depression symptom, but also an independent risk factor for recurrence. Cordyceps militaris (C. militaris) is thought to have the potential to treat insomnia. This study aimed to examine the efficacy and safety of duloxetine with C. militaris in improving sleep symptoms in patients with depression. Methods: This study was a single-center, randomized, double-blind, placebo-controlled study that recruited outpatients admitted to Beijing Anding hospital from January 2018 to January 2019. Major depressive disorder (MDD) with insomnia was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) criteria and Mini-International Neuropsychiatric Interview (M.I.N.I.). Eligible subjects will be randomly assigned to two treatment groups in a 1:1 ratio, and receive treatment and follow-up of about 6 weeks of duloxetine plus cordyceps militaris or placebo, respectively. The severity of depression and insomnia was evaluated at baseline and at 1, 2, 4, and 6 weeks using the 17-item Hamilton Depression Scale (HAMD-17) and Athens Insomnia Scale (AIS). Results: A total of 59 subjects were included in the study (31 in the placebo group and 28 in the C. militaris group). 11 (18.6%) participants withdrew during the study period, 5 (17.9%) in the C. militaris group, and 6 (19.3%) in the placebo group. Depressive and sleep symptoms in all patients reduced over time. We found that the total scores of AIS and its subscales decreased more in the placebo group compared to the C. militaris group (p < 0.05). Secondary outcome revealed that there were no significant differences between the two groups in total HAMD-17 and its sleep factor scores (p > 0.05) at 1, 2, 4, and 6 weeks after treatment initiation. The incidences of adverse events were not significantly different between the two groups (all p > 0.05). Conclusion: C. militaris at the current dose and duration did not improve sleep symptoms in patients with depression, but it is safe with rare side effects.